Dog bites and attacks on athletes: lack of effective prevention mechanisms - Muhamed Katica; Nadža Kapo; Nasreldin Hassan Ahmed; Anida Kapo-Gurda; Safet Kapo (Medicinski glasnik, 2021)
Athletes who train in public places in urban and rural areas are just as attacked and injured by dogs of known owners as they are by dogs with no owners, in a relatively equal proportion. The largest number of bites occurs in the summer, what makes up half of all bites, just when sports activity is most pronounced. Athletes who are most often exposed to potential attacks and bites are cyclists, long-distance athletes, marathon runners, recreational athletes, etc. both during training and competitions. Off-road cyclists are at a significantly higher risk of dog attacks because cycling takes place off-road, that is, away from urban areas. Dog attacks can adversely affect the psycho-physical readiness of athletes. In Bosnia and Herzegovina there have been no cases of injuries to athletes recorded by competent medical institutions or umbrella sports associations. It is necessary to work on more efficient administration (registration and recording of attacks and bites of dogs). It is of utmost importance to educate athletes on dog behaviour, the reasons for their aggressive behaviour and causal mechanisms of dog attacks as well as the first aid education, what can have a great impact on reducing further complications.
Keywords: aggression; animals; first aid; marathon running; sports